Strategi Pemasaran Pada Perumahan dengan Menggunakan Analisis Swot : (Studi Kasus Pada Perumahan Menganti Alam Raya Sentosa Gresik) - Ajeng Prasti Kumalasari; Mahjudin Mahjudin; Aridha Prassetya; Rina Dewi; Achmad Daengs (Jurnal Pengabdian Masyarakat, 2025)
Marketing strategy is one of the weapons for companies to face market competition. Basically, a marketing strategy is to find a match between the company's internal capabilities and external opportunities in the market. However, the Company also needs to recognize the strengths and weaknesses of the company in the competition. This will greatly help companies in recognizing themselves, as well as taking advantage of every opportunity that exists and avoiding or minimizing threats. Where in determining competitive strategies and making decisions, a manager must recognize what are the weaknesses, strengths, threats, opportunities that the company has and recognize the advantages of competitors that may have. Thus, the company must be able to pay attention to factors that can affect the survival of the company, both external and internal factors. In order to find the formulation of an appropriate marketing strategy, it is necessary to identify the strengths, weaknesses, opportunities and threats faced by the company. For this reason, this research was held which focuses on efforts to determine marketing strategies that are in accordance with the company's conditions in the midst of competition. The results of this study show that the company's position is in a state of growth (GROWTH) so that the strategy suggested for PT Bintang Karyasama as the housing developer of Menganti Alam Raya Semtosa is an SO strategy with an emphasis on the strategy of increasing the choice of house types with various price options. Thus, PT Bintang Karyasama as the housing developer of Menganti Alam Raya Semtosa can highlight its competitive advantage compared to other similar competitors.